Analisis Kompetensi Guru dalam Pengelolaan Kelas pada Pembelajaran Tematik Tema Hidup Bersih dan Sehat di Kelas III SDI Manumuti - Selviana Elisabeth Hoar; Yuventius Tamelab; Yanuarius Bria Seran; Damian Puling (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Learning is a process of interaction between students, educators, and learning resources in a learning environment. The effectiveness of learning is greatly influenced by the teacher's ability to manage the class. At SDI Manumuti, a third-grade teacher demonstrated good classroom management in thematic learning, especially on the theme of caring for living things. Classroom management is an important factor in creating a conducive learning atmosphere so that the learning process can take place optimally. This study aims to explore more deeply the role of teachers in managing the class in thematic learning. The study used a qualitative approach with a descriptive method. Data collection techniques included observation, documentation, and interviews, while data analysis was carried out inductively through data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers play an important role in creating and maintaining conducive classroom conditions. These efforts are carried out through two main strategies. First, teachers prioritize three aspects in learning, namely: (1) strengthening character education through discussion activities that encourage students to appear in front of the class, thereby fostering self-confidence, discipline, and activeness; (2) strengthening literacy through reading materials or stories related to the theme at the beginning of the meeting; and (3) the application of 4C skills (Creative, Critical thinking, Communicative, and Collaborative) through varied learning activities, including learning outside the classroom to avoid boredom. Second, teachers often use discussion methods to train students to express opinions, speak in front of the class, and work together. This method is considered effective in building students' self-confidence and social skills.